Distribusi Gen Enterotoksin Staphylococcus aureus dari Susu Segar dan Pangan Asal Hewan - Isrina Oktavia Salasia, Siti; -, Khusnan; -, Sugiyono (Jurnal Veteriner; Vol 10 No 3 (2009))
Staphylococcus aureus is a potential pathogen causing disease in human and animals due to severalvirulence factors. Staphylococcal enterotoxins which is responsible for foodborne disease is considered tobe one of the important virulence factor for the bacteria. The research was conducted to identify variousenterotoxin genes of S. aureus. Twenty three S. aureus isolates from milk cows (12 isolates) and foodanimal products (11 isolates) were used to study various enterotoxins genes (sea, seb, sec, sed, see, seg, seh,sei, and sej). The enterotoxins genes of S. aureus were investigated by using polymerase chain reaction(PCR) with specific primers. There were 3 isolates (13.04%) negative for staphylococcal enterotoxin genes.Twenty isolates (86.96%) harboured for one or more staphylococcal enterotoxin genes such as: sec (6 isolates/26.09%), see, seh for 1 isolate (4.35%), combination of 2 genes se (b,i), se (c,g), se (g,i) for 1 isolate of each(4.35%), se(c,e) for 2 isolates (8.70%), se(b,c) for 4 isolates (17.39%). Staphylococcal enterotoxin could bedetected in 3 combination genes of se(b,c,i), se(c,e,i), se(c,g,i) for 1 isolate of each (4.35%).
Keywords: Staphylococcus aureus, enterotoxin, fresh milk, food animal origin